Map art lab : 52 exciting art explorations in map making, imagination, and travel - Berry, Jill K.; McNeilly, Linden (Beverly, MA : Quarry Books, 2014)
"Travel through the exciting world of cartography with Map Lab. This fun and creative book features 52 map-related activities set into weekly exercises, beginning with legends and lines, moving through types and styles, and then creating personalized maps that allow you to journey to new worlds. Authors Jill K. Berry and Linden McNeilly guide readers through useful concepts while exploring colorful, eye-catching graphics. The labs can be used as singular projects or to build up to a year of hands-on creative experiences. Map Lab is the perfect book for map lovers, creative/DIY-inspired, designers. Artists of all ages and experience levels can use this book to explore enjoyable and engaging exercises. Everyone loves maps. And what's not to love? They are beautiful and fascinating, they teach you things, they show you where you are, places you long to go, and places you dare to imagine"--
Keywords: Maps in art; Map drawing -- Technique; Cartography in art